2013
DOI: 10.1007/s00586-013-3086-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of norepinephrine on spinal cord blood flow and parenchymal hemorrhage size in acute-phase experimental spinal cord injury

Abstract: Purpose In the acute phase of spinal cord injury (SCI), ischemia and parenchymal hemorrhage are believed to worsen the primary lesions induced by mechanical trauma. To minimize ischemia, keeping the mean arterial blood pressure above 85 mmHg for at least 1 week is recommended, and norepinephrine is frequently administered to achieve this goal. However, no experimental study has assessed the effect of norepinephrine on spinal cord blood flow (SCBF) and parenchymal hemorrhage size. We have assessed the effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 34 publications
2
16
0
1
Order By: Relevance
“…Within the spinal cord microenvironment, DOB+ appeared to alleviate spinal cord ischemia more effectively than NE by optimizing cord oxygenation, blood flow and metabolic indices. In contrast, NE did not modify SCBF and worsened hemorrhaging, mirroring observations from Soubeyrand et al 4 in a feline model. Several studies have linked NE with central gray matter hemorrhaging in experimental models 5,6 , which is thought to result from unfavourable blood flow redistribution in the cord microenvironment 3 .…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Within the spinal cord microenvironment, DOB+ appeared to alleviate spinal cord ischemia more effectively than NE by optimizing cord oxygenation, blood flow and metabolic indices. In contrast, NE did not modify SCBF and worsened hemorrhaging, mirroring observations from Soubeyrand et al 4 in a feline model. Several studies have linked NE with central gray matter hemorrhaging in experimental models 5,6 , which is thought to result from unfavourable blood flow redistribution in the cord microenvironment 3 .…”
Section: Discussionsupporting
confidence: 86%
“…Hemodynamic management is one of the only neuroprotective strategies available to clinicians, and current guidelines suggest that mean arterial pressure (MAP) be maintained between 85-90 mmHg with intravenous fluids and vasopressors such as norepinephrine (NE), with the aim of offsetting systemic hypotension and maintaining adequate spinal cord perfusion 2 . Though this “one-size-fits-all” strategy can improve spinal cord blood flow (SCBF), vasopressor management with NE has been shown to produce potentially harmful SCBF profiles in some acute SCI patients 3 and has been shown by multiple investigators to exacerbate intraparenchymal hemorrhage 4–6 . In the setting of acute SCI, clinical studies have shown strong associations between increased cord hemorrhaging and worsened neurological outcomes (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Animal models demonstrate that normotension should be maintained and that induced hypertension avoided given the evidence suggesting increased risk of spinal cord hemorrhage [32]. Subsequent animal models of the risk of hypertension demonstrated that norepinephrine did not improve spinal cord perfusion but was associated with increased size of parenchymal hemorrhage [33]. Kepler et al and Inoue et al found either decreased motor function with MAP > 85 mmHg or no correlation between MAP > 85 mmHg and motor recovery [34,35].…”
Section: Hypertension Detrimental For Neurological Motor Recoverymentioning
confidence: 99%
“…Зміни концентрації та конформації цих компонентів визначають виникнення значних морфофункціональних зрушень у рухових нейроцитах СМ за ДГК. Крім того, звертається увага на наявність у цих просторах медіаторів, нейрогормонів, гормонів периферичних ендокринних залоз та інших біологічно активних речовин (Nepomnjashсhih and Bakarev, 2009;Soubeyrand et al, 2014), які активізують процеси перебудови нейроцитів при ДГК.…”
Section: обговорення результатів дослідженьunclassified